A Novel Homozygous Variant of TMEM231 in a Case With Hypoplasia of the Cerebellar Vermis and Polydactyly - Wang, Tao; Liu, Yu-Xing; Luo, Fang-Mei; Dong, Yi; Li, Ya-Li; Fan, Liang-Liang (Frontiers in Pediatrics, 2021)
Background: Transmembrane protein 231 (TMEM231) is a transmembrane protein and is a component of the B9 complex participated in the formation of the diffusion barrier between the cilia and plasma membrane. Mutations in TMEM231 gene can contribute to Joubert syndrome (JBTS) or Meckel–Gruber syndromes (MKS). However, reports on JBTS or MKS caused by TMEM231 mutations are comparatively rare. Method: We described a Chinese fetus with unexplained hypoplasia of the cerebellar vermis and polydactyly detected by ultrasound imaging. The fetus was primarily diagnosed as JBTS/MKS. The parents of this fetus were non-consanguineous and were healthy. Whole-exome sequencing (WES) and bioinformatics strategies were employed to explore the genetic lesion of this family. Results: An unknown missense variant (c.19C>T;p.R7W) of TMEM231 gene was detected. The mutation was predicted as pathogenic and was absent in our 200 healthy controls. Conclusion: In total, we employed WES to explore the genetic lesion of a fetus with unexplained hypoplasia of the cerebellar vermis and polydactyly. A novel mutation in TMEM231 gene was identified. Our study not only provided data for genetic counseling and prenatal diagnosis to this family, but also broadened the spectrum of TMEM231 mutations.